407 Surgical Site Infection of Renal Transplant Patients Stratified by BMI. (19th August 2022) - Berjaoui, N; Haq, I; Hunter, J; Roy, D; Imray, C; O'Callaghan, J
Abstract: Aim: Surgical site infection increases with BMI with values ranging from 20% to greater than 40%. There are increasing numbers of obese patients (BMI >30) undergoing transplants and this audit aims to review the incidence and grade of surgical site infection (SSI) of renal transplant recipients stratified by BMI. Method: 65 renal transplants were performed between April 2020-March 2021 with 58 kidneys from deceased donors and 7 kidneys from live donors. A retrospective review of clinical attendances, GP letters, prescriptions, imaging, and re-admissions was completed. Nearly one-third of the patients had pre-transplant diabetes (32%), and their median BMI was 28 (range 19–40.7). The incidence of SSI was reported after 3 months follow up and graded using the Clavien-Dindo Classification. Results: The overall rate of SSI was 15%. SSI was 12.8% in patients with BMI<30, 15.8% in BMI 30–34.9, 33.3% in BMI 35–35.9, and 0 in BMI>40 (only one recipient). There was no significant correlation between diabetes and SSI, with 19% of SSI reported in diabetic patients versus 14% in patients without diabetes (p-value=0.7). Two patients had a Clavien-Dindo grade I infection, 1 grade II, and 7 Grade III, with no grade IV or V SSI. No patients required operative management of SSI. Conclusions: The overall rates of SSI stratified by BMI were within expected limits. Diabetes was not an independent predictor of SSI. No complication required general anesthesia or surgical treatment. When SSI did occur in obese patients it did cause considerable morbidity through number of attendances for dressing changes over 3 months.